Faktor-Faktor yang Mempengaruhi Continuance Intention Pengguna Go-Food di Jakarta - Cindy Monica; Vita Briliana (Jurnal Wira Ekonomi Mikroskil, 2019)
This study aims to determine the effect of perceived ease of use, perceived usefulness, confirmation, performance value, and satisfaction with continuance intention. The research used is in the form of casual and descriptive research. Samples taken were 142 respondents using purposive sampling technique. The data analysis method is done by SEM (Structural Equation Model) using SmartPLS 3.0 and IBM SPSS version 25. This research shows that perceived ease of use, perceived usefulness, confirmation, performance value and satisfaction have an influence on continuance intention.